Attainment of universal health coverage in the occupied Palestinian territory assessed by a general equilibrium approach: is informality an irreversible hurdle for universality?. (June 2022) - Abu-Zaineh, Mohammad; Awawda, Sameera
Abstract: Background: Achieving universal health coverage (UHC) has recently received attention in response to calls from international organisations to expand health coverage to hard-to-reach segments of the population (eg, informal workers, and unemployed and poor people). Despite the strong commitment to achieving UHC, its implementation continues to spark vigorous debate among policy makers, scholars, and the international health community. Much of the recent debate has focused on the macro-fiscal challenges that many developing countries face in implementing and sustaining UHC-oriented reforms, and there has also been debate in relation to challenges of the micro-behavioural sphere (at the level of the individual). Some of these challenges pertain to the structure of the labour market in developing countries, which is characterised by the large size of non-contributory segments of the population, mainly informal workers and unemployed individuals. This raises the important policy questions of the feasibility of expanding health coverage to the informal sector and the unemployed on a contributory basis. Methods: We assessed the feasibility of UHC using a dynamic general equilibrium approach while accounting for heterogeneity across households in terms of their employment and socioeconomic status. The model was calibrated using the Palestinian Expenditures and Consumption Survey (PECS, 2011), and the Social Accounting Matrix (SAM, 2011). We assessed alternative health insurance designs proposed to target the informal workers. Fiscal sustainability of the reforms was examined using the debt-to-GDP ratio and the microeconomic impact was assessed using the concept of consumption equivalent variation (CEV), defined as the amount of additional consumption a household would give up to move from the pre-insurance to the post-insurance level of welfare. A positive CEV value indicates that individuals are willing to pay for the health insurance. The higher the CEV value, the higher the gains of health insurance. Findings: A simultaneous expansion of UHC coverage of the population and health-care costs would enhance welfare for all households. However, such an expansion would reduce government expenditure that is allocated to other sectors; for example, it was estimated that the reduction would have been approximately 10% in 2020. To finance this UHC-driven debt, we examined the impact of a tax-financed UHC-oriented reform and a low-premium, low-coverage government-sponsored health insurance that targets informal workers. Although both policies would generate additional revenues to serve the UHC debt, government-sponsored health insurance targeting informal workers seems to be more feasible in terms of its impact on household welfare. That is, the informal workers would be better off under the government-sponsored health insurance scheme. Interpretation: In the absence of precise information on the ability to pay of informal workers, which in some cases might be comparable to that of formal workers, it is reasonable for the government to charge better-off informal workers rather than naively exempting them. The findings corroborate previous evidence suggesting that informal workers are willing to join health insurance schemes that charge them lower premiums for a slightly less generous benefit package than the health insurance schemes of formal workers. This health insurance might be deemed equitable in terms of the degree of financial protection that informal workers can obtain compared with the scenario in which they are left to bear high out-of-pocket health-care costs. Funding: The A*MIDEX project (number ANR-11-IDEX-0001-02).